2022
DOI: 10.1371/journal.pone.0273451
|View full text |Cite
|
Sign up to set email alerts
|

Loaded inter-set stretch may selectively enhance muscular adaptations of the plantar flexors

Abstract: The purpose of this study was to evaluate differences in changes in muscle strength and muscle thickness (MT) of the plantar flexor muscles between traditional resistance training (RT) involving passive rest and RT combined with inter-set stretch in the calf raise exercise. Employing a within-subject design, 21 young, healthy men performed plantar flexion exercises twice per week in both a traditional RT (TRAD) format and combined with a 20-second inter-set stretch (STRETCH). One leg was randomly assigned to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
6
1
Order By: Relevance
“…However, given that several studies have observed beneficial hypertrophic effects with no evidence of a detriment, the strategy would seem to have a good cost-benefit profile. Intriguingly, despite some research showing acute strength impairments subsequent to static stretching protocols ( 64 ), current research does not indicate deleterious effects across different populations on long-term strength outcomes and in some instances the strategy shows positive adaptations ( 59 , 62 ).…”
Section: Conclusion and Practical Applicationscontrasting
confidence: 60%
See 3 more Smart Citations
“…However, given that several studies have observed beneficial hypertrophic effects with no evidence of a detriment, the strategy would seem to have a good cost-benefit profile. Intriguingly, despite some research showing acute strength impairments subsequent to static stretching protocols ( 64 ), current research does not indicate deleterious effects across different populations on long-term strength outcomes and in some instances the strategy shows positive adaptations ( 59 , 62 ).…”
Section: Conclusion and Practical Applicationscontrasting
confidence: 60%
“…As noted, avian models of loaded stretch show greater hypertrophy in muscles comprised predominantly of type I compared to type II myofibers ( 46 ). The aforementioned study by Van Every et al ( 59 ) found that inter-set stretch elicited greater hypertrophy in the soleus, a type I dominant muscle, compared to the gastrocnemii, a mixed-fiber muscle. Replication of these findings and further research into the mechanisms of inter-set stretch is needed to better understand this phenomenon and its potential practical implications to program design.…”
Section: Conclusion and Practical Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on these, triceps surae muscle hypertrophy may be greater after standing than seated calf-raise training. Both standing and seated calf-raise are common exercises to train the triceps surae, and have been often implemented alone ( Carson et al, 2010 ; Gavanda et al, 2020 ; Kudo et al, 2020 ) or in combination ( Schoenfeld et al, 2020 ; Kataoka et al, 2022 ; Van Every et al, 2022 ) in previous studies. However, no study has compared their hypertrophic effects through training interventions.…”
Section: Introductionmentioning
confidence: 99%